Signifying the Nation: Gabriel Dumont, Harry Robinson, and the Canadian Captivity Narrative - Kim, Christine (Studies in Canadian Literature, 2003)
Gabriel Dumont's Gabriel Dumont Speaks and Harry Robinson's "Captive in an English Circus" are two very different Native-authored texts that counter the dominant narrative of nineteenth-century Canadian nationhood by offering alternative perspectives on the Northwest Rebellions. Locating these texts within the conventions of captivity narratives raises questions about the social significance of the genre by invoking both the politics of form and the form of politics. The two works critically distance the reader from the containment strategies of the captivity genre and reveal its complicity with the imperial expansionist project.